Evaluación de carotenoides y lípidos en la microalga scenedesmus dimorphus a escala laboratorio bajo condiciones de fotobiorreactor (2019)
Carotenoids are metabolites produced by microalgae, these act as accessory pigments in photosynthesis and as photoprotective molecules; therefore, in order to increase the accumulation of carotenoids in the microalga Scenedesmus dimorphus, salinity (NaCl and KNO3) and blue LED light were evaluated as stress factors when reaching the stationary phase of the growth of the crop; establishing that the most optimal salt to induce carotenogenesis in the microalgae species was KNO3 at a concentration of 0.6M, since this culture had the highest concentration of total carotenoids (0.3357 μg of carotenoids mL-1) and a color change of green to yellow, being a qualitative indicative of the presence of carotenoids. Subsequently, the process was scaled in an adapted container of 4 L, where a work volume of 3.5 L was used for the crop, which entered the stationary phase on day 12 and on day 14 the KNO3 was added at 0.6 M; this experiment lasted 20 days of cell count and on the last day by spectrophotometry a total of 0.7395 μg of carotenoids mL-1 was obtained.